Morphological Error Analysis of Muhasabah Column at Sabili Islamic Magazine - Hanafi Hanafi (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2020)
This study aims to describe the morphological errors in the Muhasabah of Sabili Islamic Magazine March 10 edition which are caused by the wrong choice of affixes, wrong rephrasing, wrong composing of compound words, and wrong choice of word forms. The research method used in this research was a qualitative method. The steps taken by the writer in analyzing the data were as follows: (1) counting the number of sentences, (2) identifying sentences, (3) analyzing errors, (4) calculating the frequency of the error, (5) calculating the percentage of error, (6) interpreting the research results, and (7) concluding the research results. The result concludes that (1) the error frequency is 23 cases; (2) the percentage of errors is 43.40%; (3) medium error category (25% - 50%); (4) the morphological error was caused by the wrong choice of affixes, the wrong use of repeating words, the wrong formulation of compound words, and the wrong form; and (5) mistakes that are often made by language users should be reduced or completely eliminated if possible.